المذاهب النظرية المكونة لنموذج سياسة الخارجية السورية - محمود يوسف; شريقي طرفة; زيتي اياد (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The foreign policy of any State, must be controlled by a combination of theories and doctrines that guide its work and give it a special character distinguish it from the other states, and Syrian foreign policy is not outside this framework, the main Theories of foreign policy, realism theory, liberalism and constructivism and doctrines subdivided of them, are govern the work of most of the political systems around world on the external level, and this research shows the most important of these theories and doctrines which formed the model and the theoretical framework of Syrian foreign policy over the past years, after identifying the basic premises and orientations and priorities of Syrian foreign policy إن أي سياسة خارجية لدولة ما، لابد أن تكون محكومة بخليط من النظريات والمذاهب التي توجه عملها وتضفي عليها طابعا خاصا بها يميزها عن الآخرين. والسياسة الخارجية السورية ليست خارج هذا الإطار، فالنظريات الرئيسة في السياسة الخارجية التي تتمثل في النظرية الواقعية والليبرالية والبنائية والمذاهب التي تتفرع عنها، هي التي تحكم عمل أغلب النظم السياسية على الصعيد الخارجي. و هذا البحث يبين أهم هذه النظريات والمذاهب التي شكلت النموذج والإطار النظري للسياسة الخارجية السورية خلال الأعوام الماضية، بعد التعرف على المنطلقات الأساسية وتوجهات وأولويات السياسة الخارجية السورية.